The deepest blue - Durst, Sarah Beth (Durst, Sarah Beth. Tales of Renthia., 2019)
Life is precious and precarious on the islands of Belene. Besieged by a capricious ocean full of malicious spirits, the people of the islands seek joy where they can. Mayara, one of the island<U+2019>s fearless oyster divers, has found happiness in love. But on the day of her wedding to the artist Kelo, a spirit-driven storm hits the island with deadly force. To save her loved ones, Mayara reveals a dangerous secret: she has the power to control the spirits. When the storm ends, she is taken into custody by the queen<U+2019>s soldiers and imprisoned with other women like her. They vary in age and social status, but to many they are heroes who will aid the country or witches that will sacrifice themselves trying. No matter who they are, the women are sent to a terrifying place<U+2014>an island filled with bloodthirsty nature spirits, and left without food, water, shelter, or any tools except their own instincts and magic. Whoever survives the Island of Testing will be declared heirs to the queen. But no matter if she wins or loses, Mayara knows that the life she dreamed of is gone.